Apakah Demografi dan Mentor Masih Penting dalam Menentukan Kesuksesan Karier Pegawai? - Roosemarina A. Rambe (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2005)
Demographic variables and mentor are known to be related to objective and subjective career success, especially to banking employees. The research objectives are to know the career success of banking employees and to know the relationship between objective career success (salary) and subjective career success (career satisfaction) with the demographic variables (age, sex, education, and marital status) and mentor. The respon¬dents are banking employees in Bengkulu city who have two years work experiences. Using canonical analysis, it proves that demographic variables and mentor are related to salary and career satisfaction. However, based on canonical loading, out of 5 independent variables, only age, marital status and sex are significant related to salary and career satisfaction.Keyword: objective career success, subjective career success, salary, career satisfaction, demography, mentor.